Pengelolaan Keuangan Dan Pengembangan Usaha Bagi Pelaku Usaha UMKM Di Desa Batuan Sukawati - Putu Pande R. Aprilyani Dewi; Ni Putu Budiadnyani; I Gusti Agung Ayu Pramita Indraswari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Most Micro, Small and Medium Enterprises (MSMEs) have difficulty managing their business finances separately from their personal finances. This combined financial management often leads to various problems, such as difficulty in monitoring business cash flow, difficulty in planning effective business finances, and lack of understanding of overall business profitability. This points to the need for a more professional approach to financial management for MSMEs to improve their business performance and sustainability.